Why Behavioral Indicators May Fail to Reveal Mental States: Individual Differences in Arousal-Movement Pattern Relationships - Toomela, Aaro; Nõmm, Sven; Kõnnussaar, Tiit; Tammik, Valdar (Frontiers in Psychology, 2019)
It is commonly assumed that behavior reflects mental states of individuals. However, recent attempts to detect human states of mind with behavioral indicators have not been always successful; behavioral indicators may be unreliable and invalid. In this study we show that one of the common behavioral indicators, change in the overall amount of movement, correlated at the group level well with changes in the skin conductance level (SCL), which reflects changes in arousal. At the individual level, however, changes in the SCL were related to movement patterns only in about half of the individuals. It is also noteworthy that the level of movement-SCL correlation was very highly predictable by certain social and cognitive characteristics of the individuals. Our results suggest that behavioral indicators may in many cases fail to predict mental states at the individual level.